BOX PLOT VISUALIZATION OF AGRO-MORPHOLOGICAL CHARACTERS IN Brassica juncea UNDER NORMAL AND SODIC CONDITIONS - Mallika Jaiswala; S.C Vimala; Baudh Bharti; Anamish Tyagi (The Bioscan, 2025)
Brassica juncea (Indian mustard), a major oilseed crop of global and national importance, exhibits considerable phenotypic plasticity across diverse agro-ecological environments. This study evaluated 176 diverse genotypes over two years (2023–24 and 2024–25) at two contrasting locations in Uttar Pradesh, India—Kumarganj (L1; normal soil) and Masaudha (L2; sodic soil). Using an alpha lattice design, phenological, morphological, and yield-related traits were assessed under open field conditions. Descriptive statistics and box plot analyses were employed to explore genotype performance and environment-induced variation. Results revealed that L1 favored early and uniform flowering (DFI, DFF, DHF), greater plant height variability, and higher productivity (biological yield, seed yield, harvest index), indicating suitability for high-input systems. In contrast, L2 exhibited wider flowering intervals and delayed maturity under stress conditions but showed more stable plant architecture and higher thousand-seed weight, suggesting better adaptation to resource-limited environments. The findings emphasize the significance of genotype × environment interaction in B. juncea and recommend exploiting complementary traits through targeted hybridization between high-yielding and stress-resilient genotypes to enhance breeding efficiency and adaptability.